ININNAWA: Pendidikan Karakter Pada Anak Dalam Tradisi Suku Bugis Di Kampung Kukup Koya Koso Kota Jayapura - Saputra, Andika Dian; Karman, Abd; Nawir, M Syukri (POROS ONIM: Jurnal Sosial Keagamaan, 2021)
This research aimed to understand the Ininnawa tradition maintained by the Bugis people of nurturing their children in Kukup Village. The method used in this research was qualitative descriptive with a social phenomenology paradigm. Research findings: the Ininnawa tradition is a tradition where has a benefit for the Bugis generation in improving and maintaining cultural preservation to keep them facing and overcoming challenges. The Ininnawa tradition aims to increase the Bugis people's ability to adapt to their surroundings. This tradition is learning to develop intellectual skills and a principle firmly entrenched in adulthood about "seriousness" and "shame" in the spirit of success. The Ininnawa tradition is a hereditary inheritance from the Bugis people that is to be done from time to time in their lives as a way of preserving the culture that has a philosophy of thinking, feeling, and believing to behavior in society, which includes Sipakatau (not distinguish each other), Sipakainge (recognizing each other), and Sipakalebbi (mutual respect). The Ininnawa tradition exemplifies personality and social attitudes in everyday life. This tradition is consistent with Islamic teachings, which aim to instill good morals by the requirements of the Qur'an and Hadith.